Validity of Ecosystem Material StoryBook Learning Media In Class V Elementary School - Lopuo, Ilan; Nusantari, Elya; Katili, Abubakar Sidik (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
A storybook is a book that contains stories about a situation or phenomenon. These circumstances or phenomena can be fact or fiction. In learning activities in elementary school story books can be used as a medium of learning for students. One of storybook utilization is in science learning. Storybooks can help the students at elementary school in learning activities as well as in school. In Science learning there is material that is absolutely contextually motivated, one of which is about the ecosystem. Ecosystem material can be the content of a story in a storybook for elementary students. The quality of a storybook that is used as a medium of learning in elementary school is determined by its validities. The aims of this study to describe the validity of learning media. The learning media is storybooks for grade V at elementary school students, in material of science especially. The subject in the study is a storybook that has been developed as a products in previous study.  This study is qualitative research with data analysis used is quantitative descriptive. Data collection using storybook learning media validation sheets. The results of this study that the analysis of Storybook Learning Media Products that have been validated has a validation score > 75% with valid criteria It means that the storybook products that have been produced can be utilized as a learning medium in ecosystem materials in grade V elementary school.